(untitled) (International Journal of Engineering and Computer Science, 2016)
In this paper a data mining schema developed to analyze human brain Autonomous Neuron Telematic metrics during its functional period. The organization of modules and their staged data process functionalities are discussed. The architecture designed helps to improve the treatment strategies as well as doctors medical diagnosis process. It acts as a recommender system with clean interfacing to raw data processing. Also the paper focuses on neuron metrics and their data acquisition techniques